The Political Thought of Nelson Mandela and the Resurgence of South Africa on the Global Stage - Abdullah, Said (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
The aftermath of World War II not only impacted the nations competing for power worldwide, but also had significant consequences for countries that were merely pawns in the war. During World War II, much of Asia and Africa were colonized by European powers. Consequently, these nations experienced significant shifts in politics, economics, and other aspects of life. Due to the exploitation of its natural resources by Europe, Africa was more devastated compared to Asia. Despite both positive and negative consequences of the Second World War, one certainty is that African societies had to laboriously work for an extended period to restore every aspect of their lives to ensure their survival in the future. Following the victory of the African National Party in the 1948 elections, South Africa was declared a white-dominated country. People of other races were denied political rights and full citizenship. The practice of Apartheid sparked protests in South Africa and worldwide. Discrimination in education, social, and cultural spheres resulted from Apartheid policies, which were opposed by the black population. Nelson Mandela was one of the prominent figures who fought against Apartheid in South Africa.